(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Freedom implies the absence of constraints; responsibility implies the assumption of limitations. In this context, education has a very important role, having the task of balancing the disadvantages of freedom with the advantages of responsibility. When one uses one’s freedom to limit the freedom of others, things degenerate. People need to be educated for responsibility; it does not develop without help. The balanced intertwining of freedom and responsibility is an act of divine greatness. The classroom is the place where the student learns how to behave in society. Teachers have a huge responsibility because they are the most important ambassadors of authentic values. An important aspect of the concern for freedom and responsibility is found in religious education. Focusing on the development of character, on the transmission of values and on the acquisition of pedagogical content that encourages the cultivation of true faith in parallel with the development of critical thinking is the most valuable way to approach the human personality.